Current Perspectives for the use of Gonane Progesteronergic Drugs in the Treatment of Central Hypoventilation Syndromes - Loiseau, Camille; Cayetanot, Florence; Joubert, Fanny; Perrin-Terrin, Anne-Sophie; Cardot, Philippe; Fiamma, Marie-Noe; Frugiere, Alain; Straus, Christian; Bodineau, Laurence (Current Neuropharmacology, 2018)
Background: Central alveolar hypoventilation syndromes (CHS) encompass neurorespiratory diseases resulting from congenital or acquired neurological disorders. Hypercapnia, acidosis, and hypoxemia resulting from CHS negatively affect physiological functions and can be lifethreatening. To date, the absence of pharmacological treatment implies that the patients must receive assisted ventilation throughout their lives. Objective: To highlight the relevance of determining conditions in which using gonane synthetic progestins could be of potential clinical interest for the treatment of CHS. Methods: The mechanisms by which gonanes modulate the respiratory drive were put into the context of those established for natural progesterone and other synthetic progestins. Results: The clinical benefits of synthetic progestins to treat respiratory diseases are mixed with either positive outcomes or no improvement. A benefit for CHS patients has only recently been proposed. We incidentally observed restoration of CO2 chemosensitivity, the functional deficit of this disease, in two adult CHS women by desogestrel, a gonane progestin, used for contraception. This effect was not observed by another group, studying a single patient. These contradictory findings are probably due to the complex nature of the action of desogestrel on breathing and led us to carry out mechanistic studies in rodents. Our results show that desogestrel influences the respiratory command by modulating the GABAA and NMDA signaling in the respiratory network, medullary serotoninergic systems, and supramedullary areas. Conclusion: Gonanes show promise for improving ventilation of CHS patients, although the conditions of their use need to be better understood.
Keywords: progesterone